2019
DOI: 10.1002/er.4489
|View full text |Cite
|
Sign up to set email alerts
|

Further progress in the research of fin‐based passive cooling technique for the free‐standing silicon photovoltaic panels

Abstract: Summary The paper deals with a passive air‐based cooling technique of photovoltaic (PV) panels in operating conditions. Cooling technique is done by specific type of using aluminium fins, and its main purpose is to increase the electrical efficiency of the PV panel. An increase in electrical efficiency can be achieved because of temperature degradation effect, where the PV panel yields less power at higher operating temperatures (the PV panel's efficiency can drop by up to 0.5%/°C). To confirm a cooling techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Research by Grubišić-Čabo [26,27] showed a similar trend of increasing efficiency with aluminum fins mounted on the backside of a PV panel (Si-poly, 50 Wp). Semiconductor properties in solar cells are similar to temperature-sensitive electronic devices.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Research by Grubišić-Čabo [26,27] showed a similar trend of increasing efficiency with aluminum fins mounted on the backside of a PV panel (Si-poly, 50 Wp). Semiconductor properties in solar cells are similar to temperature-sensitive electronic devices.…”
mentioning
confidence: 69%
“…Research by Luo et al [25] used an experimental method to demonstrate several heat sinks with flared fin configurations and obtained an overall reduction in thermal resistance of up to 10%. Research by Grubišić-Čabo et al [26,27] examined the aluminum fins mounted on the backside of a PV panel (Si-poly, 50 Wp). The results showed that, under low wind conditions, the electrical efficiency of solar cells increases by 0.3% and 0.2% under solar irradiation of 850 W/m 2 and 500 W/m 2 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of the research is to investigate the techno-economic viability of different energy concepts in order to secure a suitable mix of energy technologies that would support an efficient energy transition. An improvement in the energy efficiency of different renewable energy technologies is also important, especially in the case of photovoltaics ( Grubišić-Čabo et al., 2019 ) and wind generation technologies ( Marinić-Kragić et al., 2020 ), to secure large scale projects. The efficiency of specific production processes ( Giama et al., 2020 ), is also vital and certainly needs to be carefully investigated and analysed, to reduce energy intensity and provide a circular economy concept in specific application areas, ( Xu et al., 2020 ).…”
Section: Iot Technologies In Sustainable Energy and Environmentmentioning
confidence: 99%
“…Several potential solutions that address the need for solar cell thermal management have been proposed [15][16][17][18][19]. These solutions involve the integration of PV cells with thermal management modules, the combination of which is known as photovoltaic thermal (PVT) systems.…”
Section: Introductionmentioning
confidence: 99%
“…These systems use air cooling or water cooling to cool the solar cells and increase their electrical output. For example, a water spray application over PV panel surfaces [17] and a fin-based passive cooling technique [18] were investigated as practical demonstrations for solar cell cooling. Furthermore, the advantages of integrated PVT systems over conventional solar energy plants that consist of both PV modules and solar collectors were also investigated in depth not only from a thermodynamic energy perspective [19] but also an economic perspective with regards to the installation and operation of these systems.…”
Section: Introductionmentioning
confidence: 99%